PENATALAKSANAAN FISIOTERAPI DAN TERAPI LATIHAN PADA KASUS POST ORIF MANUS DIGITI IV SINISTRA - Mutiara Putri, Salsabilla Kharisma; Amanati, Suci (Jurnal Keperawatan dan Kesehatan, 2026)
Background: Fracture of the manus digiti is a traumatic injury that can cause pain, limited range of motion (ROM), decreased muscle strength, and impaired functional activity, especially in post Open Reduction Internal Fixation (ORIF) conditions. These problems require appropriate physiotherapy management to restore optimal hand function. Objective: This study aimed to analyze physiotherapy management using exercise therapy and to evaluate clinical outcomes in a patient with post-ORIF manus digiti IV sinistra. Methods: This study employed a case report design with a pre–post approach without a control group. The subject was a 19-year-old male patient treated at Dr. Kariadi General Hospital, Semarang. Interventions included passive exercise, active exercise, resisted active exercise, static contraction, and hold-relax exercise, conducted over four therapy sessions. Data were collected using the Visual Analog Scale (VAS) for pain, a goniometer for range of motion (ROM), and Manual Muscle Testing (MMT) for muscle strength. Data analysis was performed descriptively by comparing results before and after intervention. Results: The results showed a reduction in tenderness and movement pain, as well as improvements in range of motion in the MCP, PIP, and DIP joints, and increased muscle strength following the exercise therapy interventions. Conclusion: Physiotherapy management using exercise therapy is effective in reducing pain, improving range of motion, and increasing muscle strength in post-ORIF manus digiti IV sinistra patients, thereby enhancing functional ability.